Wideband end-fire antenna based on modulated grooved surface plasmon polaritons - Amitkumar Patel; Aakash Bansal; Chinthana Panagamuwa; William Whittow (Scientific Reports)
Abstract This article presents low-profile wideband millimeter-wave (mmWave) end-fire antenna based on groundless grooved spoof surface plasmon polaritons (SSPPs) technique for applications in 5G mmWave communications. A novel linearly modulated grooved profile has been designed and optimized to convert bounded SSPP modes into radiation modes. The proposed groundless modulated grooved profile is designed to achieve a zero tilting and highly directional beam in the end-fire direction. A semi-curvilinear ground profile and stepped impedance transition profile are designed to improve impedance matching, which simultaneously enable wide bandwidth of 22 GHz to 41 GHz, i.e., fractional bandwidth (FBW) of 62% with a peak gain of 13 dBi in a low-profile structure. The overall form-factor of the antenna is 5 $$λ _{0}$$ $$×$$ 0.9 $$λ _{0}$$ $$×$$ 0.016 $$λ _{0}$$ (where $$λ _{0}$$ is the wavelength in free space at the center frequency). The high directivity, low-profile and lightweight structure of the antenna makes it highly suitable for applications in mmWave communications.